2015
DOI: 10.1021/es5050453
|View full text |Cite
|
Sign up to set email alerts
|

Does the Current Fungicide Risk Assessment Provide Sufficient Protection for Key Drivers in Aquatic Ecosystem Functioning?

Abstract: The level of protection provided by the present environmental risk assessment (ERA) of fungicides in the European Union for fungi is unknown. Therefore, we assessed the structural and functional implications of five fungicides with different modes of action (azoxystrobin, carbendazim, cyprodinil, quinoxyfen, and tebuconazole) individually and in mixture on communities of aquatic hyphomycetes. This is a polyphyletic group of fungi containing key drivers in the breakdown of leaf litter, governing both microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 52 publications
7
65
2
Order By: Relevance
“…This seems worrying given that detritus can be a significant sink for metals and organic contaminants (e.g., Bundschuh et al, 2013;Sridhar et al, 2001;Zubrod et al, 2015a). To safeguard the integrity of aquatic ecosystems, it thus seems necessary that prospective risk assessments cover all significant exposure routes including dietary uptake.…”
Section: Resultsmentioning
confidence: 99%
“…This seems worrying given that detritus can be a significant sink for metals and organic contaminants (e.g., Bundschuh et al, 2013;Sridhar et al, 2001;Zubrod et al, 2015a). To safeguard the integrity of aquatic ecosystems, it thus seems necessary that prospective risk assessments cover all significant exposure routes including dietary uptake.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the 'leaf conditioning' by bacteria and fungi is an indispensable prerequisite for the feeding activity of shredding invertebrates (Bärlocher and Kendrick, 1975;Cummins et al, 1973), with the fungal community composition determining the leaf palatability Suberkropp, 1984, 1989;Suberkropp et al, 1983;Gulis and Suberkropp, 2003). Hence, fungicides acting on the microbial decomposers indirectly affect the habitat or food choices of shredding invertebrates Flores et al, 2014;Rasmussen et al, 2012aRasmussen et al, , 2012bZubrod et al, 2011Zubrod et al, , 2015, and the reduction of shredders has been linked to a slow-down of leaf decomposition processes (e.g., Flores et al, 2014;Rasmussen et al, 2008;Wallace et al, 1982). In the present study, shredders were found at sites with and without Carbofuran impact, at mean proportions of 19% (total of taxa) and 21% (total of SPEAR).…”
Section: Concentration-response Dependence and Compounds Responsible mentioning
confidence: 99%
“…As shown, for instance, by Arsuffi and Suberkropp [23], shredders distinguish between fungal species on leaf litter, potentially triggered by the production of feeding stimulants or distasteful compounds. This concept was recently applied to explain fungicide-induced shifts in microorganism-mediated leaf palatability for Gammarus fossarum [3, 24], a key shredder in low-order streams of Europe [45]. The study of Zubrod et al [3], however, was based on spore counts, which does not necessarily correlate with the biomass of the respective aquatic hyphomycete species [10].…”
Section: Resultsmentioning
confidence: 99%
“…This concept was recently applied to explain fungicide-induced shifts in microorganism-mediated leaf palatability for Gammarus fossarum [3, 24], a key shredder in low-order streams of Europe [45]. The study of Zubrod et al [3], however, was based on spore counts, which does not necessarily correlate with the biomass of the respective aquatic hyphomycete species [10]. Applying qPCR could result in deeper insights into shredder food preferences by estimates of single-species biomasses linked to prior knowledge of preferred species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation